Working with children and youth with complex needs 20 skills to build resilience - Ungar, Michael, 1963- (London : Routledge, 2021)
This new edition of Working with Children and Youth with Complex Needs provides detailed descriptions of techniques, ample case studies, fascinating and easy to understand explanations of research, and rich stories of how social workers, psychologists, counselors, child and youth care workers, and other mental health professionalscan help young people become more resilient. Fully updated and including new discussions of trauma, adverse childhood experiences (ACEs), resilience, genetic susceptibility to stress, the impact of migration and natural disasters on families, and much more, Dr. Ungar shows why we need to work just as hard changing the environments that surround children as we do changing children themselves. Building on lessons learned from clinical, community and residential settings, Dr. Ungar discusses a shortlist of 20 essential skills that can enhance the effectiveness of frontline mental health services without relying on expensive, resource heavy programs. Along with descriptions of the skills necessary to talk with clients about the factors that put their mental health at risk, Working with Children and Youth with Complex Needs presents systemic practices clinicians can use in their everyday work to help their clients transform their worlds and improve their access to the resources they need to succeed. Chapters present a variety of practical strategies that clinicians can use to enhance and sustain the therapeutic value of their work, including engaging with children's extended family; addressing issues of community violence, racism and homophobia; and helping parents and teachers understand (and change) children's maladaptive coping strategies. A series of videos accompanies the text to help readers see the skills that are discussed being applied to real-life situations mental health professionals and their community allies encounter.
OCLC-licensed vendor bibliographic record.
Keywords: Resilience (Personality trait) in children; Resilience (Personality trait) in adolescence; Social work with children; Social work with youth; Child psychotherapy; Adolescent psychotherapy; PSYCHOLOGY / Psychotherapy / Child & Adolescent; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychopathology / Post-Traumatic Stress Disorder (PTSD)